Association of Lipid Profile and Liver Parameters with Different Grades of Non-alcoholic Fatty Liver Disease - Drutpal Baghel; Kapila Gaikwad; Vedika Rathore; Ravindra Saxena; Rahul Dubey; Yar Ansari (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: The present study aimed to determine lipid profile and liver function tests in patients with non-alcoholic fatty liver disease (NAFLD) and examine their possible association with various degrees of NAFLD.Material and methods: Fifty patients with NAFLD were enrolled in this cross-sectional study, and their serum lipids and liver parameters were analyzed.Results: Serum total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL) levels were increased in 54%, 68%, 42%, and 38% of NAFLD patients, respectively. Serum high-density lipoprotein (HDL) levels were decreased in 36% of NAFLD patients. Similarly, serum aspartate transaminase (AST), alanine transaminase (ALT), and total bilirubin were increased in 60%, 58%, and 52% of NAFLD patients, respectively whereas total protein levels were decreased in 38% of NAFLD patients. Increasing grades of NAFLD were substantially associated with increasing serum TC, TG, VLDL, AST, ALT, and total bilirubin. At the same time, HDL and total protein levels were decreasing.Conclusions: A dyslipidemic pattern of lipid markers and abnormal liver function tests were observed in patients with NAFLD. Dyslipidemia and increased AST and ALT levels were also associated with increasing degrees of fatty liver in patients with NAFLD.